Maltrato y problemas emocionales en adolescentes - Adriana Carolina Sánchez Acosta (2021)
The research was as objective to identify, through a literature review, the relationship between maltreatment and emotional problems during adolescence. The methodology had a qualitative approach; likewise, an analytical-synthetic method and the type of study was a documentary, descriptive, and correlational nature. The sample was intentional, non-probabilistic, consisting of 47 scientifically valid articles selected from an initial universe of 111 articles in line with the theme of this work, with the ACC greater than 1.50, valid SJR impact factor, and year of publication between 2010 and 2020. Besides, scientific articles come from databases such as Elsevier, Dialnet, Google Scholar, Researchgate, Scielo, Scopus, and Redalyc. As a result, it was shown that the most frequent types of abuse are physical, psychological, emotional, negligence, abandonment, and sexual abuse; and the most common emotional problems in adolescents are anxiety and depression, all this without leaving aside behavioral problems; concluding in this way that abuse causes the appearance of emotional problems during adolescence.